Application of the Experimental Method for Carbohydrate Content in Healthy and Nutritious Food Materials in Increasing Student Motivation at SDI Mutiara Islam Al Ittiba' - Viera Setyani; Farida Catur Wahyu Anggriyani, M. Pd (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2024)
Science learning often uses the lecture method which makes students less enthusiastic about learning. The aim of this research is to find out how the learning process works by applying experimental methods for carbohydrate content in healthy and nutritious food. This research uses interview and observation methods. Based on the results of research that has been carried out, it is easier for students to understand the material by using the experimental method. The experimental method is proven to provide experience and involve students directly in activities.